Research progress in nursing of multiple myeloma complicated by peripheral neuropathy (多发性骨髓瘤并发周围神经病变患者的护理研究进展) - LI Lixia (李丽霞); BAN Jinchun (班锦青); LIANG Jinglin (梁静林); NONG Zhenzhen (农珍诊); WEI Ling (韦玲) (中西医结合护理)
Peripheral neuropathy is a common complication during treatment of multiple myeloma, which affecting the prognosis and patients’ quality of life. Effective prevention, treatment and nursing interventions have been proved to reduce the incidence of multiple myeloma complicated by peripheral neuropathy. This paper reviewed the studies on nursing of multiple myeloma complicated by peripheral neuropathy in perspectives of risk factors, prevention, treatment and nursing interventions, in order to provide reference for clinical nursing practice. (多发性骨髓瘤周围神经病变(MMPN)是多发性骨髓瘤(MM)治疗过程中常见的并发症之一, 严重影响患者的生活质量及预后, 有效的预防措施、治疗方法和护理干预均能有效降低MMPN的发生率。本研究从MMPN的危险因素、预防、治疗及护理干预措施进行综述, 旨在为MMPN患者的护理提供参考依据和实践指导。)